Controllable synthesis for fabrication of micro/nano-structured mesoporous precursor particles for high performance lithium-ion batteries - Dong, Bin (2018)
Increasingly global warming and air pollution caused by the consumption of fossil fuel have imposed the priority of using green energy. As a result, the use of rechargeable lithium-ion batteries (LIBs) has increased rapidly Olivine-structured LiFePO4 is considered as one of the most promising positive electrode materials owing to its significant advantages of nontoxicity, low cost of raw materials, good structural stability at high temperature, excellent safety performance, and relatively high theoretical specific capacity (170 mAhg-1) with a flat discharge-charge potential (3.45V vs. Li+/Li). Therefore, LiFePO4 battery becomes a reliable material for energy storage system used in hybrid electric vehicles (HEVs), full electric vehicles (EVs), plug-in hybrid electric vehicles (PHEVs), and portable devices. However, the poor rate performance of LiFePO4, resulting from its intrinsic low Li+ diffusivity (10-17 to 10-14 cm2s-1) and low electronic conductivity (10-9 to 10-8 S cm-1), has become a technical bottleneck to confine its widely practical applications. Following previous studies, a systematic study on controllable preparation of LiFePO4 positive electrode material with nanoscale size, or hierarchical micro/nano mesoporous structure has been carried out using various synthesis methods, including impinging stream reaction (ISR), ultrasonic-intensified impinging stream reaction (UISR), two-step co-precipitation method, and two-step hydrothermal method (UIHT). The physical and chemical properties of as-synthesized products are measured by XRD, FTIR, SEM, TEM, BET, Mastersizer, CV, and charge-discharge test. Based on these observations, the relationship among particle morphology, electrochemical performance, and impacts of fluid dynamics is evaluated in this work.